2012
DOI: 10.15232/s1080-7446(15)30354-5
|View full text |Cite
|
Sign up to set email alerts
|

Calving date and wintering system effects on cow and calf performance I: A systems approach to beef production in the Nebraska Sandhills

Abstract: A 4-yr study using 217 cows/yr (3/4 Red Angus, 1/4 Simmental)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…Fallborn calves had lighter WW (P < 0.05) in 3 regions (the Cornbelt, North, and Rocky Mountains), all located in colder climates. These findings were similar to results of a lesser magnitude observed in the Nebraska Sandhills (Griffin et al, 2012). Lighter WW for fallborn calves could be caused by feeding poorer-quality, harvested forages to lactating cows during their greatest nutritional demand, which coincided with harsh winters in this region.…”
Section: Statistical Analyses For a Subset Of The Databasesupporting
confidence: 82%
See 1 more Smart Citation
“…Fallborn calves had lighter WW (P < 0.05) in 3 regions (the Cornbelt, North, and Rocky Mountains), all located in colder climates. These findings were similar to results of a lesser magnitude observed in the Nebraska Sandhills (Griffin et al, 2012). Lighter WW for fallborn calves could be caused by feeding poorer-quality, harvested forages to lactating cows during their greatest nutritional demand, which coincided with harsh winters in this region.…”
Section: Statistical Analyses For a Subset Of The Databasesupporting
confidence: 82%
“…Some seasonal weight contrasts were greater than 100 kg and may have a substantial economic impact for cattlemen. Earlier studies found significant seasonal effects with a magnitude of 10 to 25 kg, although some were from previous decades (Bagley et al, 1987;Gaertner et al, 1992;Griffin et al, 2012;Caldwell et al, 2013). The modern beef cow is biologically very different from the cow of the 1990s, and the offspring have greater genetic potential for growth.…”
Section: Statistical Analyses For a Subset Of The Databasementioning
confidence: 98%
“…Grazing strategies across the globe are quite diverse from low-intensity management of pastoral and communal approaches to high-intensity management facilitated by infrastructure developments (Roche et al 2015). Key management practices that have been developed include (1) the application of sustainable stocking rates to maintain or improve the health of rangelands, including riparian habitats (Briske et al 2011), as well as associated optimization of net income (Holechek 2013;Kemp et al 2013), and (2) matching of calving season to the prevailing environment to reduce associated harvested feed costs (Grings et al 2005;Griffin et al 2012). …”
Section: Technological Advancesmentioning
confidence: 99%
“…Subirrigated meadows at GSL are dominated by cool season grasses, including slender wheatgrass [ Elymus trachycaulus (Link) Matte], redtop bent ( Agrostis stolenifera L.), timothy ( Phleum pretense L.), Kentucky bluegrass ( Poa pratensis L.), and smooth bromegrass ( Bromus inermus Leyss.) ( Griffin et al, 2012 ). Average annual precipitation at GSL from 2005 to 2017 was 54.09 cm with an SD of 16.60 cm.…”
Section: Methodsmentioning
confidence: 99%